Radical scavenging activity of steviol glycosides, steviol glucuronide, hydroxytyrosol, metformin, aspirin and leaf extract of Stevia rebaudiana - Hajihashemi, Shokoofeh; M.C. Geuns, Jan (Free Radicals and Antioxidants)
Introduction: Reactive oxygen species (ROS), generated in many bioorganic redox processes, are the most dangerous by-products in the aerobic environment. The aim of this study was to compare the in vitro antioxidant activity of some chemical compounds and leaf extract of Stevia rebaudiana as natural antioxidant. Methods: The radical scavenging activity of ascorbic acid, quercetine, stevioside (ST), rebaudioside A (Reb A), steviol glucuronide (SVglu), glucose, sucrose, hydroxytyrosol, metformin and aspirin were measured and expressed as the inhibitory concentration in mM giving 50% reduction of radicals (IC50). Results: Ascorbic acid, quercetine, ST, Reb A, SVglu, glucose, sucrose, hydroxytyrosol, metformin and aspirin were active OH scavengers. Superoxide radicals were efficiently scavenged by ascorbic acid, SVglu, quercetine, hydroxytyrosol, ST, Reb A and aspirin. Quercetine, hydroxytyrosol, ascorbic acid and aspirin were active in limiting the amount of thiobarbituric acid (TBA) reactive material. Only ascorbic acid, quercetine and hydroxytyrosol showed DPPH and NO scavenging activity. Leaf extract of S. rebaudiana had an excellent ROS scavenging activity. Treatment of leaf extracts with PVPP and active charcoal removed a part of their scavenging activity. Results showed that sugars were not efficient ROS scavengers. Conclusion: Radical scavenging activity of steviol derivatives, aspirin, metformin and hydroxytyrosol might explain most of beneficial pharmacological effects on ROS related diseases, such as hypertension, type 2 diabetes, atherosclerosis, inflammation and certain forms of cancers. The results obtained in this study indicate that leaf extract of S. rebaudiana has a great potential to use as a natural antioxidant agent.
Keywords: DPPH; NO; OH; Superoxide; TBA reactive material